IMPLEMENTASI METODE KARAKTERISTIK DALAM PEMBELAJARAN BAHASA ARAB DI SMK MUHAMMADIYAH PAGELARAN: Indonesia - Abi Rifai; Amrulloh Khoirul Ma'arif; Salamun (Jurnal Pendidikan Bahasa Arab L-DHAD, 2022)
Abstract The characteristic method is a method of determining the subject that aims to determine the character and morality of karimah. This characteristic method is important in learning languages, especially Arabic. This characteristic method triggers the growth of the spirit of learning that has a contribution in promoting ahlakul karimah in learning Arabic. This article describes a case that occurred at SMK Muhammadiyah Pagelaran, regarding the low moral character of students in teaching and learning Arabic. This study aims to determine the implementation of the characteristic method in improving students' character in learning Arabic at SMK Muhammadiyah Pagelaran and its advantages and disadvantages. The method in this study uses a qualitative method, where this research procedure produces descriptive data in the form of written and spoken words of people who are used as informants. Data collection techniques in this study were through in-depth interviews, participant observation and document review. The results of this study include: 1) Exemplary, 2) Creating an atmosphere of value and ethical systems in schools, and 3) Internalizing values and ethics in learning Arabic. This shows that the analysis of the data found by using the characteristic method in learning Arabic at SMK Muhammadiyah Pagelaran is good. However, it needs to continue to be evaluated so that new innovations emerge that can be applied so that everything goes well and in accordance with what is expected by all parties. Keywords: Characteristics Method, Arabic Learning